The Effect of Electronic Word of Mouth, Trust, Perceived Risk, and Site Quality on Transactions using E-Commerce - Tunjung Candra Ervia Danis; Budi Istiyanto; Elia Ardyana (International Conferences SDGs 2030 Challenges and Solutions, 2030)
This study examines the effect of electronic word of mouth, trust, risk perception, and site quality on transactions using e-commerce. The sampling technique using proportional random sampling method with the sample amount of 100 people. Data analysis techniques used to answer the hypothesis is multiple regression using SPSS 16.00 for Windows. The result of research shows that there is a significant positive effect of electronic word of mouth on the interest of transactions using e-commerce, there is a significant positive effect of trust on the interest of transact using e-commerce, there is a significant negative effect of risk perception on the interest of transact using e-commerce, Positively significant site quality to transact interest using e-commerce.